Phosphorus foliar fertilization in guava trees - Natale, W. [UNESP]; Coutinho, E. L M [UNESP]; Banzatto, D. A. [UNESP]; Boaretto, A. E. (My University, 2002)
Currently there is very little information on the response of fruiting perennial plants to applied P. This is especially true for tropical production areas where soils have a high capacity of P fixation, and are poor in native phosphorus. An alternative to soil P fertilization, which is inefficient in fixing soils, is to apply phosphorus as a foliar spray. P is quickly absorbed by leaves, and is redistributed quite well through the plants because its phloem mobility, and foliar application may be a viable practice. The purpose of this present work, is to determine the effectiveness of foliar P application on the nutritional status and yield of guava. The experiment was done in a Typic Hapludox, for three consecutive agricultural years, in an adult orchard of 'Paluma' guava. Five treatments were tested: four rates leaf applications of P (0-0.5-1.0 and 2.0% of P2O5) and a control where P was applied to soil (200 g of P2O5/plant). Through the results it was verified that the foliar application of P altered the concentration of the nutrient in the soil (13 to 48 mg dm-3 P-resin), and in the guava leaves (1.2 to 1.8 g of P kg-1), but did not affect the production of fruits. In conclusion, in field conditions, it is viable to combine the phosphorus foliar fertilization with disease control, without increasing the operations and, consequently, the production cost.
Keywords: Fruit crop; Nutrition; Orchard; P foliar; Psidium guajava